Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/pharmaceutics13101729
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Fluid Volume and Distribution in the Paediatric Colon via Magnetic Resonance Imaging

Abstract: Previous studies have used magnetic resonance imaging (MRI) to quantify the fluid in the stomach and small intestine of children, and the stomach, small intestine and colon of adults. This is the first study to quantify fluid volumes and distribution using MRI in the paediatric colon. MRI datasets from 28 fasted (aged 0–15 years) and 18 fluid-fed (aged 10–16 years) paediatric participants were acquired during routine clinical care. A series of 2D- and 3D-based software protocols were used to measure colonic fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 69 publications
(136 reference statements)
1
9
1
Order By: Relevance
“…Since then, multiple differences in physiology and biopharmaceutics between children and adults have been identified [1,11]. With respect to the GI environment in children, exploratory studies have already shown that it differs from the adult environment considering pH, bile salt content, osmolality, and fluid volume [1,[12][13][14]. However, more extensive research is needed to expand and validate the limited physiological reference data currently available and to integrate these physiological data into reliable simulation tools and models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, multiple differences in physiology and biopharmaceutics between children and adults have been identified [1,11]. With respect to the GI environment in children, exploratory studies have already shown that it differs from the adult environment considering pH, bile salt content, osmolality, and fluid volume [1,[12][13][14]. However, more extensive research is needed to expand and validate the limited physiological reference data currently available and to integrate these physiological data into reliable simulation tools and models.…”
Section: Introductionmentioning
confidence: 99%
“…While MRI has been extensively used in the past to determine GI fluid volumes in adults, its use is now being extended to the pediatric population, with two recent smallscale studies analyzing the stomach and small intestine (SI) (32 fasted children, aged 0-16 years) and the colon (28 fasted children, aged 0-15 years) [13,14]. The limited data currently available show both a high variability in fluid volumes among children and important differences compared to adults.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic resonance imaging has shown that fluid pockets may predominately be found in the caecum, ascending colon, and descending colon [121]. In children, free colonic fluid volume is lower than adults and does not vary according to biological sex [122]. Clinical studies show that low solubility drugs are poorly absorbed in the colon, a finding that may be exacerbated by the colon's low availability of free fluid [88].…”
Section: Luminal Fluid and Gasmentioning
confidence: 99%
“…Although data are relatively scarce, significantly lower volumes of GI fluids have been reported in paediatrics compared to adults (Goelen et al, 2021;Papadatou-Soulou et al, 2019). Obviously, altered GI volumes may affect drug dissolution and even impact BCS/DCS drug classification.…”
Section: Integration Of Biorelevant Gi Volumes Into Dissolution Testingmentioning
confidence: 99%